Strategies to control invasive mussels:: a review (INNOTEC, 2022)
The biofouling process can damage various man-made structures, and together with ballast water are the main vectors for the transfer of organisms around the world. The control of invasive species, especially mussels, has been debated for a long time, but all techniques have limitations. Therefore, the purpose of this review was to collect information on the advances in research on invasive mussel control. The database Periódicos CAPES was used, searching for the keywords: "(invasive mussel biofouling) AND control". Fifty-three articles were analyzed from 1999 to 2020. It was identified that more experimental studies have been carried out in fresh water than in other systems. Most were performed in the laboratory compared to the field, involving the juvenile and adult phases of the mussel. The chemical control was the most discussed in the analyzed literature in comparison with the physical and biological controls. Among the types of chemical control, the use of natural extracts stands out, as it is effective and causes less damage to the environment.
Keywords: macrofouling; antifouling; predation; UV ligth; natural extracts